Implikasi Yuridis Free Retribution Toilet Umum Pada Stasiun Pengisisian Bahan Bakar Umum (SPBU) di Kota Yogyakarta (Studi Surat Edaran Menteri BUMN Nomor SE-16/MBUT11/2021) - Bagus Anwar Hidayatulloh (Jurnal Hukum Sasana, 2022)
This study examines the juridical implications related to the free retribution of public toilets at gas stations in the city of Yogyakarta based on the Circular Letter of the Minister of SOEs Number SE-16/MBUT11/2021 concerning Quality Improvement of Public Facilities and SOE Social Facilities. The retribution made by several gas stations has become a separate polemic among the public, especially since the Minister of SOEs conducted inspections at several gas stations, so that not long after, a Ministerial Circular Letter appeared regarding the quality of service for public facilities and social facilities in SOEs. The impact of the Circular is also on the City of Yogyakarta which has 16 gas stations in collaboration with SOEs. So that raises the formulation of the problem what are the implications of the Circular Letter of the Minister of SOEs SE-16/MBUT11/2021 regarding Quality Improvement of Public Facilities and Social Facilities of SOEs and what are the legal implications of free retribution for toilets based on the Circular of the Minister of SOEs Number SE-16/MBUT11/2021 and the constraints faced in the implementation of the Circular of the Minister of SOEs Number SE-16/MBUT11/2021. The purpose of this study was to determine the juridical implications of the application of free retribution toilets at gas stations in Yogyakarta City and can be used as material for evaluating the implementation of the SOE Ministerial Circular.